2003
DOI: 10.1152/jn.00557.2002
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Movements: Behavioral Studies of Blinking in Humans Under Different Stimulus Conditions

Abstract: The kinematics and neurophysiological aspects of eyelid movements were examined during spontaneous, voluntary, air puff, and electrically induced blinking in healthy human subjects, using the direct magnetic search coil technique simultaneously with electromyographic recording of the orbicularis oculi muscles (OO-EMG). For OO-EMG recordings, surface electrodes were attached to the lower eyelids. To measure the vertical lid displacement, a search coil with a diameter of 3 mm was placed 1 mm from the rim on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
120
1
6

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 40 publications
11
120
1
6
Order By: Relevance
“…It is difficult to measure the blinking duration from corneal data, and we could not find any reference to validate our results. However, from eyelid motion, we measured blinking with an average duration of 0:307 AE 0:106 s, which is consistent with values found by VanderWerf et al [9] and Nakamura et al [10], who reported durations of 0.334 and 0:320 s, respectively.…”
supporting
confidence: 91%
“…It is difficult to measure the blinking duration from corneal data, and we could not find any reference to validate our results. However, from eyelid motion, we measured blinking with an average duration of 0:307 AE 0:106 s, which is consistent with values found by VanderWerf et al [9] and Nakamura et al [10], who reported durations of 0.334 and 0:320 s, respectively.…”
supporting
confidence: 91%
“…To test this trivial possibility, we compared the cortical activations evoked by a spontaneous eyeblink and those evoked by comparable physical blackouts (165 ms in duration) (14) that were inserted in the same video clips pseudorandomly with a mean interval of 6.4 s. The DMN exhibited greater activation after an eyeblink than after a blackout ( Fig. 3A and Table S3), clearly showing that the transient activation in the DMN was due to the eyeblink per se and not to the physical interruption of the visual input.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the optimal blink onset and offset thresholds, a lid "velocity" (i.e., change in arbitrary units/time) was computed. Because eye blinks are characterized by an extremely high eyelid velocity (VanderWerf et al 2003), the measured times of blink onset and offset were relatively insensitive to changes in thresholds. Thus the thresholds could easily be set to a high enough value to exclude most eyelid movements that were not blinks.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary version of this study has been published previously in abstract form (Walton and Gandhi 2005).…”
Section: Introductionmentioning
confidence: 99%